Towns and cities - Aldis, Rodney (New York Dillon Press, 1992)
Examines urban plants and animals, their survival techniques in the city, and methods of keeping them from being endangered.
"First published by Evans Brothers Limited ... London"--T.p. verso.
Includes index.
Keywords: Urban ecology (Biology) -- Juvenile literature; Urban animals; Urban plants; Urban ecology (Biology); Ecology